An update on nonsteroidal anti-inflammatory drugs and gastrointestinal risk - Jacky van Schoor (South African Family Practice, 2014)
Recommendations for the prevention of nonsteroidal anti-inflammatory drug (NSAID)-related gastrointestinal ulceration and cardiovascular (CV) complications were recently made available through an initiative designed in collaboration with leading specialists in South Africa. The prevention of CV complications and NSAID-related ulceration are discussed in two articles for the purposes of this publication. The first article in this two-part series presented an update on NSAID-related CV risk. This is the second article, and provides an update on NSAIDs and gastrointestinal risk.